Eksplorasi Tantangan Pengembangan Kinerja Penelitian dan PKM Dosen di Universitas Pamulang: Pendekatan Manajemen SDM - Hendry Susanto; Susanto Susanto; M. Hilman Zainuri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Lecturers in many private universities in Indonesia continue to face persistent obstacles that limit their research and community engagement performance, particularly high teaching loads, limited institutional support, and insufficient research competencies. These conditions create a strategic gap, as few studies examine how human resource management (HRM) systems can effectively strengthen academic productivity in private higher education. This study aims to explore the challenges and supporting factors influencing research and community service performance among lecturers at Universitas Pamulang using an HRM perspective. Employing a qualitative phenomenological design, data were collected through semi-structured interviews with 15 lecturers, supported by documentation review and non-participatory observation. The data were analyzed using the Miles, Huberman, and Saldaña model. The findings highlight five key developments: growing methodological competence, the emergence of collaborative research practices, clearer institutional support mechanisms, stronger motivation to publish in accredited journals, and a more structured performance management system. These results indicate that lecturer performance is shaped by the alignment of competence development programs, motivational drivers, and institutionally guided performance expectations. This study contributes to existing literature by offering context-specific insight into how HRM practices may enhance research productivity within developing private universities, while providing practical recommendations for strengthening academic support systems.